Pretreatment With Bacillus cereus Preserves Against D-Galactosamine-Induced Liver Injury in a Rat Model - Li, Ya-Ting; Ye, Jian-Zhong; Lv, Long-Xian; Xu, Hong; Yang, Li-Ya; Jiang, Xian-Wan; Wu, Wen-Rui; Shi, Ding; Fang, Dai-Qiong; Bian, Xiao-Yuan; Wang, Kai-Cen; Wang, Qiang-Qiang; et al. (Frontiers in Microbiology, 2019)
Bacillus cereus (B. cereus) functions as a probiotic in animals, but the underlying mechanisms remain unclear. We aim to evaluate the protective effects and definite mechanism by which orally administered B. cereus prevents D-galactosamine (D-GalN)-induced liver injury in rats. Twenty-one Sprague–Dawley rats were equally assigned into three groups (N = 7 animals per group). B. cereus ATCC11778 (2 × 109 colony-forming units/ml) was administered to the B. cereus group via gavage, and phosphate-buffered saline was administered to the positive control (PC) and negative control (NC) groups for 2 weeks. The PC and B. cereus groups received 1.1 g/kg D-GalN via an intraperitoneal injection to induce liver injury. The blood, terminal ileum, liver, kidney and mesenteric lymph nodes (MLNs) were collected for histological examinations and to evaluate bacterial translocation. Liver function was also determined. Fecal samples were collected for deep sequencing of the 16S rRNA on an Illumina MiSeq platform. B. cereus significantly attenuated D-GalN-induced liver injury and improved serum alanine aminotransferase (ALT) and serum cholinesterase levels (P < 0.05 and P < 0.01, respectively). B. cereus modulated cytokine secretion, as indicated by the elevated levels of the anti-inflammatory cytokine interleukin-10 (IL-10) in both the liver and plasma (P < 0.05 and P < 0.01, respectively) and the substantially decreased levels of the cytokine IL-13 in the liver (P < 0.05). Pretreatment with B. cereus attenuated anoxygenic bacterial translocation in the veins (P < 0.05) and liver (P < 0.05) and upregulated the expression of the tight junction protein 1. The gut microbiota from the B. cereus group clustered separately from that of the PC group, with an increase in species of the Ruminococcaceae and Peptococcaceae families and a decrease in those of the Parabacteroides, Paraprevotella, and Desulfovibrio families. The potential probiotic B. cereus attenuated liver injury by restoring the gut flora balance and enhancing the intestinal barrier function.